Detection of Salmonella pathogenicity island and Salmonella plasmid virulence genes in Salmonella Enteritidis originated from layer and broiler farms in Java Island - Andesfha, Ernes; Indrawati, Agustin; Mayasari, Ni Luh Putu Ika; Rahayuningtyas, Irma; Jusa, Istiyaningsih (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The incidence of salmonellosis in humans and animals is still high due to the occurrence of virulence factors in Salmonella enterica which play a role in the process of infection in the host and the spread of disease and most of the S. enterica can infect humans and animals. The present study was aimed to identify Salmonella Enteritidis and detect virulence genes related to Salmonella pathogenicity islands (SPIs) and Salmonella plasmid virulence (Spv). Materials and Methods: A total of 27 S. Enteritidis archive isolates belonging to the National Veterinary Drug Assay Laboratory (NVDAL) were used in this study. The bacteria were collected in 2016 and 2017 from samples of the cloaca and fecal swabs from layer and broiler farms in five provinces of Java Island. Isolates were cultured in specific media, biochemical tests and Gram staining. Detection of S. Enteritidis and virulence genes was done by polymerase chain reaction (PCR) method. Results: Identification of serovar showed 100% (27/27) isolates were positive for the sdfI gene (304 bp). The result confirmed that all strains were S. Enteritidis. PCR based detection of virulence genes showed that 100% of isolates had virulence genes in SPI-1 to SPI-5, namely, invA, ssaQ, mgtC, spi4D, and pipA genes. All the isolates (27/27) were also positive to spvB gene-based PCR. Conclusion: All the isolates of S. Enteritidis in this study carry virulence genes related to SPI-1 to SPI-5 and plasmid virulence. The existence of virulent genes indicates that the S. Enteritidis strain examined in this study is highly virulent and poses a potential threat of worse disease outcome in humans and animals. J. Adv. Vet. Anim. Res., 6(3): 384-393, September 2019